The Effect of Vitamin D Supplementation in Children With Asthma: A Meta-Analysis - Hao, Meiqi; Xu, Ruoxin; Luo, Nachuan; Liu, Miaowen; Xie, Junping; Zhang, Wenxiong (Frontiers in Pediatrics, 2022)
Background An increasing number of studies have suggested that vitamin D can be used to treat childhood asthma, but its clinical effects are still unclear. We conducted this meta-analysis to examine the latest estimates of the effectiveness and safety of using vitamin D to treat childhood asthma. Methods The PubMed, The Cochrane Library, ScienceDirect, Embase, Scopus, Ovid MEDLINE, Web of Science, and Google Scholar databases were searched for randomized controlled trials (RCTs) describing vitamin D supplementation interventions for asthmatic children. Asthma exacerbation, vitamin D levels, the predicted percentage of forced expiratory volume in the first second (FEV1%) and adverse effects (AEs) were analyzed as the main outcome measures. Results After screening, eight RCTs with 738 children were included. Compared with placebos, vitamin D supplementation had a stronger effect on serum vitamin D levels [mean difference (MD) = 13.51 (4.24, 22.79), p = 0.004]. The pooled results indicated that no significant changes were found between the groups in asthma control, as measured by adopting the following indicators: asthma exacerbation [risk ratio (RR) = 0.92 (0.68, 1.25), p = 0.60]; Childhood Asthma Control Test (CACT) scores [MD = 0.15 (−0.43, 0.74), p = 0.61]; hospitalizations for asthma exacerbation [RR = 1.20 (0.48, 2.96), p = 0.70]; acute care visits [RR = 1.13 (0.77, 1.65), p = 0.63]; steroid use [RR = 1.03 (0.41, 2.57), p = 0.95]; and fractional exhaled nitric oxide (FeNO) [MD =-3.95 (−22.87, 14.97), p = 0.68]. However, vitamin D supplementation might reduce the FEV1% [MD = −4.77 (−9.35, −0.19), p = 0.04] and the percentage of predicted forced vital capacity (FVC%) [MD =-5.01 (−9.99, −0.02), p = 0.05] in patients. Subgroup analysis revealed no difference in AEs between the two groups. Conclusions Vitamin D supplementation significantly increased patients' serum vitamin D levels, but it had no benefit for asthma control. However, vitamin D supplementation might reduce patients' lung function. It is essential to systemically search for more large-scale, rigorous, and well-designed RCTs to fully confirm these conclusions. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021288838, PROSPERO CRD42021288838.